The efficacy and safety of probiotics in the adjuvant treatment of psoriasis: a systematic review and meta-analysis of randomized controlled trials - Zhu, Yiran; Xu, Fan; Chen, Hao; Zheng, Quanhui (Frontiers in Medicine, 2024)
Background: It has been reported that the imbalance of gut microbiota is involved in the pathogenesis of psoriasis. We retrieved randomized placebo-controlled trials to evaluate the efficacy and safety of probiotic administration in the treatment of psoriasis.The outcomes were changes in Psoriasis Area and Severity Index (PASI), Dermatology Life Quality Index (DLQI), and serum inflammatory indicators after treatment, and adverse events (AEs).Risk ratios (RRs) and mean differences (MDs) were calculated using random or fixed effects model.Seven qualified studies were identified in our study. The pooled percentage of patients with ≥75% reduction from baseline in PASI was higher in the probiotic group than that in the placebo group (33.57% vs. 23.61%; RR 1.40, p=0.06). Compared with the placebo group, the PASI (MD -3.09, 95% CI -5.04 –0.74, p=0.01) and CRP level (MD -2.36, 95% CI -2.77–1.95, p<0.0001) were significantly reduced in the probiotic group. There was no significant difference in DLQI p=0.59) and AEs (RR 0.68, p=0.22) between the two groups.Oral administration of probiotics can improve psoriasis; however, large randomized controlled trials are needed to support this conclusion.